RAGS14-033-0096 /Novel method in fabrication of micro magnetometer for low magnetic field detection - Sulaiman, Nadzril (2018)
Magnetic field plays an important role in today’s application. From medical to military purposes, all use the concept of magnetism. Many researchers have involved in designing a suitable instrument to detect different level of magnetism. These devices are known as magnetometer. Magnetometer can be used to detect the magnetization of ferromagnetic element and strength of earth magnetic field. Different type of magnetometer can detect different level of magnetic field. Such magnetometers are search coil, fluxgate, optically pumped, nuclear precession, SQUID, Hall-effect, anisotropic magnetoresistance, giant magnetoresistance, magnetic tunnel junctions, giant magnetoimpedance, magnetostrictive/piezoelectric composites, magnetodiode, magnetotransistor, fiber optic, magnetooptic, and microelectromechanical systems-based magnetic sensors. Among the magnetometers, search-coil is the simplest magnetometer that is used to detect low level magnetic fields. It is made of two components; coil and core. Today’s trend state that an ideal device should be portable, light and easy to store, thus this is where the concept of micro magnetometer came. Miniaturization governs the size, cost, reliability and power consumption. A specific tools and environment is needed through the process. The process used is similar to the fabrication of micro electromechanical systems (MEMS) devices. The purpose of this research is to study the MEMS fabrication technique of micro magnetometer. All related issues on magnetometer such as possible fabrication processes, components, and operating principles were studied. It is to select the less complex and compatible technique that is suitable for the fabrication of micro-scale search coil magnetometer.